N-type Mg3Sb2-based thermoelectric material and preparation method thereof
By regulating the Mg content and doping Ta elements, the Mg vacancy defects and grain boundary problems in Mg3Sb2-based thermoelectric materials are solved, and the N-type conductive properties and high ZT values of the material are achieved, which improves its thermoelectric properties and stability.
Patent Information
- Application Number
- CN202411859349.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
During the preparation process of Mg3Sb2-based thermoelectric materials, there are a large number of Mg vacancy defects, which affects their electrical transport performance and stability. The presence of grain boundaries leads to a decrease in thermal conductivity and electrical performance.
By regulating the Mg content, the loss of Mg during the preparation process is compensated, the Mg vacancy defect is reduced, the material is converted from P-type conductivity to stable N-type conductivity, and the Ta element is doped in the material to fill the Mg vacancy and reduce the lattice thermal conductivity.
The ZT value of the material was significantly improved from 1636% to 1.32, and further through Ta doping to 1.85, synergistic optimization of electrical and thermal properties was achieved.
Smart Images

Figure CN119751064A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy materials, and specifically relates to an N-type Mg3Sb2-based thermoelectric material and a preparation method thereof. Background Art
[0002] Green energy technology and energy efficiency improvement are important directions for global sustainable development. Thermoelectric materials are a type of functional materials that can achieve direct conversion of thermal energy and electrical energy. They have broad application prospects in waste heat recovery, precision refrigeration, and aerospace power supplies. Thermoelectric performance is characterized by the thermoelectric figure of merit ZT, and its formula is: ZT=S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. The ZT value directly affects the energy conversion efficiency. However, since S, σ, and κ are all closely related to the carrier concentration, it is difficult to achieve their coordinated optimization. Therefore, developing new materials and proposing reasonable performance control strategies are crucial to improving the efficiency of thermoelectric devices.
[0003] Among many thermoelectric materials, Mg3Sb2-based Zintl compounds are considered to be highly promising candidate materials due to their unique advantages. Compared with traditional thermoelectric materials (such as PbTe and Bi2Te3), Mg3Sb2-based thermoelectric materials have the following significant advantages: First, its constituent elements magnesium and antimony are abundant in the earth's crust, and no toxic elements are involved in the material preparation process, which has good environmental compatibility and economy; secondly, through element doping and crystal structure regulation, the material exhibits excellent ZT values in the medium temperature region (300K-700K), especially the comprehensive thermoelectric performance after N-type doping is more advantageous.
[0004] However, there are still some problems with Mg3Sb2-based thermoelectric materials, which limit their development. First, the inherent Mg vacancy defects in the material itself. Due to the high volatility of magnesium, a large number of Mg vacancies are inevitably generated during the material preparation process. This defect affects the electrical transport performance of the material on the one hand, and the stability of the material on the other hand, limiting the further development and application of its thermoelectric devices. Secondly, there are a large number of grain boundaries in the microstructure of Mg3Sb2. Although these grain boundaries can reduce the lattice thermal conductivity, they also hinder the transport of carriers, resulting in a decrease in electrical performance. How to optimize the grain boundaries to achieve a balance between electrical conductivity and thermal conductivity is one of the key research directions at present.
[0005] In view of the above problems, the present invention proposes an effective method for preparing N-type Mg3Sb2-based thermoelectric materials. By optimizing the preparation process and regulating defects, the ZT value and stability of the material are significantly improved, providing technical support for its practical application in the fields of waste heat recovery and precision refrigeration. Summary of the invention
[0006] The present invention aims to overcome the defects and deficiencies of the prior art and provide an N-type Mg3Sb2-based thermoelectric material and a preparation method thereof. The present invention adjusts the Mg content, compensates for the loss of Mg in the preparation process, reduces the Mg vacancy defects, and converts Mg3Sb2 from P-type conductivity to stable N-type conductivity. The ZT value of the P-type Mg3Sb2-based thermoelectric material is only 0.076, while the ZT value of the N-type material can reach 1.32, which is an increase of 1636%. In addition, by doping the Ta element in the N-type Mg3Sb2-based thermoelectric material, its performance is further significantly improved. The introduction of the Ta element not only fills the inherent Mg vacancies, reduces the internal defects of the material, and improves the carrier mobility, thereby enhancing the electrical performance and maintaining a high power factor; it also generates a Ta metal phase and a secondary phase in the matrix, forms a phonon scattering center, enhances phonon scattering, and significantly reduces the lattice thermal conductivity. Through the synergistic optimization of electrical and thermal properties, the material prepared by the present invention achieves a maximum ZT value of 1.85, an increase of 38.5%.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: An N-type Mg3Sb2-based thermoelectric material, the chemical composition of the Mg3Sb2-based thermoelectric material is: Mg 3+ x Ta y Sb 1.5 Bi 0.49 Te 0.01 , wherein 0.2<x≤0.6, 0<y<0.3, preferably, 0.2<x≤0.4, 0<y≤0.25.
[0008] The method for preparing the above-mentioned N-type Mg3Sb2-based thermoelectric material comprises the following steps: (1) Ingredients: According to the chemical formula Mg 3+x Ta y Sb 1.5 Bi 0.49 Te 0.01 , weigh Mg powder, Sb powder, Bi powder, Te powder and Ta powder as reaction raw materials; (2) ball milling of raw materials: the reaction raw materials weighed according to step (1) are placed in a stainless steel ball mill, the ball mill is filled with inert gas and sealed, and the sealed ball mill is placed on a three-dimensional pendulum ball mill for ball milling to obtain powder; (3) Sintering: The powder obtained by ball milling according to step (2) is loaded into a graphite mold and placed in a spark plasma sintering furnace for plasma sintering to obtain a circular sheet material with good density, which is the N-type Mg3Sb2-based thermoelectric material.
[0009] As a preferred technical solution, all steps (1) to (3) are carried out in a glove box filled with argon gas, wherein the oxygen concentration in the glove box is less than 0.1 ppm and the water concentration is less than 0.1 ppm.
[0010] As a preferred technical solution, in step (2), in addition to the reaction raw materials, two stainless steel balls with a diameter of 12 mm and two stainless steel balls with a diameter of 8 mm are placed in the ball mill to crush and mix the raw materials.
[0011] As a preferred technical solution, in step (2), the ball milling time is 12 hours, and the raw materials adhering to the ball mill jar are scraped off in the glove box every 4 hours. The entire ball milling process needs to be repeated twice.
[0012] As a preferred technical solution, the ball milling in step (2) uses a MSK-SFM-3-II three-dimensional swing ball mill, wherein the rotation speed of the ball mill is 1000 r / min.
[0013] As a preferred technical solution, the ball milling procedure in step (2) is: first rotate forward for 15 minutes, stop for 1 minute, then rotate reversely for 15 minutes and stop for 1 minute. The above is one cycle, and a total of 8 cycles.
[0014] As a preferred technical solution, in step (3), the spark plasma sintering temperature is 750°C, the pressure is 50 MPa, and the sintering time is 10 min.
[0015] As a preferred technical solution, the pressurization rate in step (3) is 15-20 MPa / min, and the heating rate is 100°C / min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adjusts the Mg content to fill the inherent Mg vacancy defects, thereby achieving stable N-type conductive performance.
[0017] 2. By doping with Ta elements, the existence of Mg vacancies can be further reduced, internal defects can be significantly reduced, carrier mobility can be improved, and better electrical properties can be obtained.
[0018] 3. The introduction of Ta element generates Ta metal phase and secondary phase in the matrix, forming phonon scattering centers, enhancing phonon scattering and significantly reducing lattice thermal conductivity.
[0019] 4. The present invention adopts the method of ball milling + hot pressing, which is simple to operate, low in cost, and easy to realize industrial mass production.
[0020] 5. Through the coordinated optimization of electrical and thermal properties, the material of the present invention achieves a maximum ZT value of 1.85. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following is a brief introduction to the drawings used in the embodiments or the prior art description. Obviously, the following drawings are only some embodiments of the present invention, and ordinary technicians in this field can also obtain other related drawings based on these drawings without creative work.
[0022] Figure 1 is a graph showing the change in conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Example 1 with temperature; Figure 2 is a graph showing the variation of the Seebeck coefficient of the N-type Mg3Sb2-based thermoelectric material prepared in Example 1 with temperature; Figure 3 is a graph showing the power factor of the N-type Mg3Sb2-based thermoelectric material prepared in Example 1 as a function of temperature; Figure 4 is a graph showing the variation of thermal conductivity and lattice thermal conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Example 1 with temperature; Figure 5 is a graph showing the variation of the ZT value of the N-type Mg3Sb2-based thermoelectric material prepared in Example 1 with temperature; Figure 6 is a graph showing the change in electrical conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Example 2 with temperature; Figure 7 is a graph showing the variation of the Seebeck coefficient of the N-type Mg3Sb2-based thermoelectric material prepared in Example 2 with temperature; Figure 8 is a graph showing the power factor of the N-type Mg3Sb2-based thermoelectric material prepared in Example 2 as a function of temperature; Fig. 9 is a graph showing the variation of thermal conductivity and lattice thermal conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Example 2 with temperature; Fig.10 is a graph showing the variation of the ZT value of the N-type Mg3Sb2-based thermoelectric material prepared in Example 2 with temperature; Fig.11 is a graph showing the change in conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Example 3 with temperature; Fig.12 is a graph showing the variation of the Seebeck coefficient of the N-type Mg3Sb2-based thermoelectric material prepared in Example 3 with temperature; Fig.13 is a graph showing the power factor of the N-type Mg3Sb2-based thermoelectric material prepared in Example 3 as a function of temperature; Fig.14 is a graph showing the variation of thermal conductivity and lattice thermal conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Example 3 with temperature; Fig.15 is a graph showing the variation of the ZT value of the N-type Mg3Sb2-based thermoelectric material prepared in Example 3 with temperature; Fig.16 is a graph showing the change in conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 1 with temperature; Fig.17 is a graph showing the variation of the Seebeck coefficient of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 1 with temperature; Fig.18 This is a graph showing the power factor of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 1 as a function of temperature; Fig.19 is a graph showing the variation of thermal conductivity and lattice thermal conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 1 with temperature; Fig. 20 is a graph showing the variation of the ZT value of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 1 with temperature; Fig.21 is a graph showing the change in conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 2 with temperature; Fig. 22 is a graph showing the variation of the Seebeck coefficient of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 2 with temperature; Fig.23 This is a graph showing the power factor of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 2 as a function of temperature; Fig.24 is a graph showing the variation of thermal conductivity and lattice thermal conductivity of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 2 with temperature; Fig.25 This is a graph showing the variation of the ZT value of the N-type Mg3Sb2-based thermoelectric material prepared in Comparative Example 2 with temperature. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 An N-type Mg3Sb2-based thermoelectric material is prepared according to the following steps: (1) Ingredients: According to Mg 3+x Ta y Sb 1.5 Bi 0.49 Te0.01 The raw materials are weighed according to the chemical formula of Mg, Sb, Bi and Te, wherein x=0.4 and y=0; and the mass purity of the elements Mg, Sb, Bi and Te is better than 99.9%.
[0025] (2) Ball milling of raw materials: In a glove box filled with argon (oxygen concentration ≤ 0.1 ppm, water concentration ≤ 0.1 ppm), the raw materials obtained in step (1) and four stainless steel balls (two with a diameter of 12 mm and two with a diameter of 8 mm) were sealed in a stainless steel ball mill. Subsequently, the ball mill was placed on a three-dimensional pendulum ball mill for oscillation and crushing, and the speed of the ball mill was set to 1000 r / min. The ball milling procedure was: forward rotation for 15 minutes, stop for 1 minute; reverse rotation for 15 minutes, and then stop for 1 minute. This was one cycle, and the ball milling was performed for a total of 8 cycles. The total ball milling time was 12 hours. Every 4 hours, the raw materials attached to the wall of the ball mill were scraped off in the glove box. The whole ball milling process required scraping twice.
[0026] (3) Sintering: The powder obtained in step (2) was loaded into a graphite mold with a diameter of 12.7 mm and placed in a spark plasma sintering furnace. During the sintering process, the pressure was increased at a pressure rate of 20 MPa / min, the temperature was increased at a heating rate of 100°C / min, and finally the temperature was kept at 750°C and an axial pressure of 50 MPa for 10 minutes. After the sintering was completed, the pressure was reduced at the same rate, and the sample was cooled to room temperature to obtain a high-density sample.
[0027] The Mg obtained in this example 3.4 Sb 1.5 Bi 0.49 Te 0.01 Thermoelectric performance test of materials such as Figure 1-4 The relationship between conductivity and Seebeck coefficient and temperature is shown in Figure 1 and Figure 2 The conductivity of the sample at room temperature is 404.6 S / cm, the Seebeck coefficient is -194.8 μV / K, the conductivity at 723K is 162.5 S / cm, the Seebeck coefficient is -286.8 μV / K, and the Seebeck coefficient is negative in the entire temperature range, indicating that it is N-type. Its power factor is shown in Figure 3 , the power factor at room temperature is 15.4 μW cm -1 mK -2 , the power factor at 723K is 13.4μW cm -1 mK -2 The relationship between thermal conductivity and lattice thermal conductivity and temperature is shown in Figure 4 , the total thermal conductivity at room temperature is 1.09 Wm -1 K -1 , the lattice thermal conductivity is 0.88 Wm -1 K -1; The total thermal conductivity at 737K is 0.73 Wm -1 K -1 , the lattice thermal conductivity is 0.55 Wm -1 K -1 . Figure 5 The variation of ZT value with temperature is shown. The highest ZT value of this sample reaches 1.32.
[0028] Compared with Comparative Example 1, this embodiment converts Mg3Sb2 from P-type conductivity to stable N-type conductivity by adding excess Mg. The ZT value of the P-type Mg3Sb2-based thermoelectric material is only 0.076, while the ZT value of the N-type material can reach 1.32, an increase of 1636%. This result further proves that the introduction of compensatory excess Mg is crucial to obtain excellent N-type Mg3Sb2 materials.
[0029] Example 2 An N-type Mg3Sb2-based thermoelectric material is prepared according to the following steps: (1) Ingredients: According to Mg 3+x Ta y Sb 1.5 Bi 0.49 Te 0.01 The raw materials are weighed according to the chemical formula of Mg, Sb, Bi, Te and Ta, wherein x=0.4 and y=0.1; and the mass purity of the elements Mg, Sb, Bi, Te and Ta is better than 99.9%.
[0030] (2) Ball milling of raw materials: In a glove box filled with argon (oxygen concentration ≤ 0.1 ppm, water concentration ≤ 0.1 ppm), the raw materials obtained in step (1) and four stainless steel balls (two with a diameter of 12 mm and two with a diameter of 8 mm) were sealed in a stainless steel ball mill. Subsequently, the ball mill was placed on a three-dimensional pendulum ball mill for oscillation and crushing, and the speed of the ball mill was set to 1000 r / min. The ball milling procedure was: forward rotation for 15 minutes, stop for 1 minute; reverse rotation for 15 minutes, and then stop for 1 minute. This was one cycle, and the ball milling was performed for a total of 8 cycles. The total ball milling time was 12 hours. Every 4 hours, the raw materials attached to the wall of the ball mill were scraped off in the glove box. The whole ball milling process required scraping twice.
[0031] (3) Sintering: The powder obtained in step (2) was loaded into a graphite mold with a diameter of 12.7 mm and placed in a spark plasma sintering furnace. During the sintering process, the pressure was increased at a pressure rate of 20 MPa / min, the temperature was increased at a heating rate of 100°C / min, and finally the temperature was kept at 750°C and an axial pressure of 50 MPa for 10 minutes. After the sintering was completed, the pressure was reduced at the same rate, and the sample was cooled to room temperature to obtain a high-density sample.
[0032] The Mg obtained in this example 3.4 Ta0.1 Sb 1.5 Bi 0.49 Te 0.01 Thermoelectric performance test of materials such as Figure 6-10 The relationship between conductivity and Seebeck coefficient and temperature is shown in Figure 6 and Figure 7 The conductivity of the sample at room temperature is 438.4 S / cm, the Seebeck coefficient is -180.7 μV / K, the conductivity at 723K is 154.4 S / cm, the Seebeck coefficient is -299.3 μV / K, and the Seebeck coefficient is negative in the entire temperature range, indicating that it is N-type. Its power factor is shown in Figure 8 The power factor at room temperature is 14.3 μW cm -1 mK -2 , the power factor at 723K is 13.8 μW cm -1 mK -2 The relationship between thermal conductivity and lattice thermal conductivity and temperature is shown in Fig. 9 , the total thermal conductivity at room temperature is 1.06 Wm -1 K -1 , the lattice thermal conductivity is 0.83 Wm -1 K -1 ; The total thermal conductivity at 737K is 0.68 Wm -1 K -1 , the lattice thermal conductivity is 0.52 Wm -1 K -1 Its ZT value changes with temperature as follows Fig.10 As shown, the highest ZT value can reach 1.46.
[0033] Compared with Example 1, the addition of a small amount of Ta element does not significantly improve the electrical properties, mainly because the doping content is insufficient and can only partially fill the high-density Mg vacancy defects inside the material. In contrast, the thermal properties are improved. The introduction of Ta element generates Ta metal phase and secondary phase, forms phonon scattering centers, enhances phonon scattering, and significantly reduces lattice thermal conductivity.
[0034] Example 3 An N-type Mg3Sb2-based thermoelectric material is prepared according to the following steps: (1) Ingredients: According to Mg 3+x Ta y Sb 1.5 Bi 0.49 Te 0.01 The raw materials are weighed according to the chemical formula of Mg, Sb, Bi, Te and Ta, wherein x=0.4 and y=0.25; and the mass purity of the elements Mg, Sb, Bi, Te and Ta is better than 99.9%.
[0035] (2) Ball milling of raw materials: In a glove box filled with argon (oxygen concentration ≤ 0.1 ppm, water concentration ≤ 0.1 ppm), the raw materials obtained in step (1) and four stainless steel balls (two with a diameter of 12 mm and two with a diameter of 8 mm) were sealed in a stainless steel ball mill. Subsequently, the ball mill was placed on a three-dimensional pendulum ball mill for oscillation and crushing, and the speed of the ball mill was set to 1000 r / min. The ball milling procedure was: forward rotation for 15 minutes, stop for 1 minute; reverse rotation for 15 minutes, and then stop for 1 minute. This was one cycle, and the ball milling was performed for a total of 8 cycles. The total ball milling time was 12 hours. Every 4 hours, the raw materials attached to the wall of the ball mill were scraped off in the glove box. The whole ball milling process required scraping twice.
[0036] (3) Sintering: The powder obtained in step (2) was loaded into a graphite mold with a diameter of 12.7 mm and placed in a spark plasma sintering furnace. During the sintering process, the pressure was increased at a pressure rate of 20 MPa / min, the temperature was increased at a heating rate of 100°C / min, and finally the temperature was kept at 750°C and an axial pressure of 50 MPa for 10 minutes. After the sintering was completed, the pressure was reduced at the same rate, and the sample was cooled to room temperature to obtain a high-density sample.
[0037] The Mg obtained in this example 3.4 Ta 0.25 Sb 1.5 Bi 0.49 Te 0.01 Thermoelectric performance test of materials such as Figure 11-15 The relationship between conductivity and Seebeck coefficient and temperature is shown in Fig.11 and Fig.12 The conductivity of the sample at room temperature is 600.1 S / cm, the Seebeck coefficient is -178.2μV / K, the conductivity at 723K is 220.4 S / cm, the Seebeck coefficient is 284.7μV / K, and the Seebeck coefficient is negative in the entire temperature range, indicating that it is N-type. Its power factor is shown in Fig.13 , the power factor at room temperature is 19.1 μW cm -1 mK -2 , the power factor at 723K is 17.9μW cm -1 mK -2 The relationship between thermal conductivity and lattice thermal conductivity and temperature is shown in Fig.14 , the total thermal conductivity at room temperature is 0.85 Wm -1 K -1 , the lattice thermal conductivity is 0.52 Wm -1 K -1 ; The total thermal conductivity at 737K is 0.70 Wm -1 K -1 , the lattice thermal conductivity is 0.45 Wm -1 K -1Its ZT value changes with temperature as follows Fig.15 As shown, the highest ZT value can reach 1.85.
[0038] Compared with Example 1 and Example 2, increasing the Ta doping concentration significantly improves the thermoelectric performance. On the one hand, the introduction of the Ta element effectively reduces the internal defects of the material and significantly improves the carrier mobility, thereby enhancing the electrical performance. On the other hand, the higher concentration of Ta aggregation and the generation of secondary phases increase the number of phonon scattering centers, further reducing the lattice thermal conductivity. Finally, compared with Example 1, the ZT value increased by 38.5%.
[0039] Comparative Example 1 An N-type Mg3Sb2-based thermoelectric material is prepared according to the following steps: (1) Ingredients: According to Mg 3+x Ta y Sb 1.5 Bi 0.49 Te 0.01 The raw materials are weighed according to the chemical formula of Mg, Sb, Bi and Te, wherein x=0.2 and y=0; and the mass purity of the elements Mg, Sb, Bi and Te is better than 99.9%.
[0040] (2) Ball milling of raw materials: In a glove box filled with argon (oxygen concentration ≤ 0.1 ppm, water concentration ≤ 0.1 ppm), the raw materials obtained in step (1) and four stainless steel balls (two with a diameter of 12 mm and two with a diameter of 8 mm) were sealed in a stainless steel ball mill. Subsequently, the ball mill was placed on a three-dimensional pendulum ball mill for oscillation and crushing, and the speed of the ball mill was set to 1000 r / min. The ball milling procedure was: forward rotation for 15 minutes, stop for 1 minute; reverse rotation for 15 minutes, and then stop for 1 minute. This was one cycle, and the ball milling was performed for a total of 8 cycles. The total ball milling time was 12 hours. Every 4 hours, the raw materials attached to the wall of the ball mill were scraped off in the glove box. The whole ball milling process required scraping twice.
[0041] (3) Sintering: The powder obtained in step (2) was loaded into a graphite mold with a diameter of 12.7 mm and placed in a spark plasma sintering furnace. During the sintering process, the pressure was increased at a pressure rate of 20 MPa / min, the temperature was increased at a heating rate of 100°C / min, and finally the temperature was kept at 750°C and an axial pressure of 50 MPa for 10 minutes. After the sintering was completed, the pressure was reduced at the same rate, and the sample was cooled to room temperature to obtain a high-density sample.
[0042] The Mg obtained in this comparative example 3.2 Sb 1.5 Bi 0.49 Te 0.01 Thermoelectric performance test of materials such as Figure 16-20 The relationship between conductivity and Seebeck coefficient and temperature is shown in Fig.16 and Fig.17 The conductivity of the sample at room temperature is 0.42S / cm, the Seebeck coefficient is 37.8μV / K, the conductivity at 723K is 1.84S / cm, the Seebeck coefficient is 194.7μV / K, and the Seebeck coefficient is positive in the entire temperature range, indicating that it is P-type. Its power factor is shown in Fig.18 , the power factor at room temperature is only 0.00057μW cm -1 mK -2 , the power factor at 723K is 0.7μW cm -1 mK -2 The relationship between thermal conductivity and lattice thermal conductivity and temperature is shown in Fig.19 , the total thermal conductivity at room temperature is 0.741 Wm -1 K -1 , the lattice thermal conductivity is 0.74 Wm -1 K -1 ; The total thermal conductivity at 737K is 0.651 Wm -1 K -1 , the lattice thermal conductivity is 0.63 Wm -1 K -1 Its ZT value changes with temperature as follows Fig. 20 As shown, the highest ZT value is 0.076.
[0043] In Comparative Example 1, although x=0.2 has reached the Mg excess range, its thermoelectric performance has not been significantly improved, which indicates that the loss of Mg is real in the preparation process. When x increases to 0.4, an effective Mg compensation effect is achieved. It can be seen that through the experimental results of Comparative Example 1, the introduction of compensatory excess Mg (x=0.4) plays a key role in improving the performance of the material. Compared with Example 1, the Mg3Sb2 thermoelectric material without Mg compensation exhibits P-type conductivity, and its ZT value is only 0.076. This is mainly due to the presence of a large number of Mg vacancy defects in the P-type Mg3Sb2 material. This result further proves that the introduction of compensatory excess Mg is crucial to obtain excellent N-type Mg3Sb2 materials.
[0044] Comparative Example 2 An N-type Mg3Sb2-based thermoelectric material is prepared according to the following steps: (1) Ingredients: According to Mg 3+x Ta y Sb 1.5 Bi 0.49 Te 0.01 The raw materials are weighed according to the chemical formula of Mg, Sb, Bi, Te and Ta, wherein x=0.4 and y=0.3; and the mass purity of the elements Mg, Sb, Bi, Te and Ta is better than 99.9%.
[0045] (2) Ball milling of raw materials: In a glove box filled with argon (oxygen concentration ≤ 0.1 ppm, water concentration ≤ 0.1 ppm), the raw materials obtained in step (1) and four stainless steel balls (two with a diameter of 12 mm and two with a diameter of 8 mm) were sealed in a stainless steel ball mill. Subsequently, the ball mill was placed on a three-dimensional pendulum ball mill for oscillation and crushing, and the speed of the ball mill was set to 1000 r / min. The ball milling procedure was: forward rotation for 15 minutes, stop for 1 minute; reverse rotation for 15 minutes, and then stop for 1 minute. This was one cycle, and the ball milling was performed for a total of 8 cycles. The total ball milling time was 12 hours. Every 4 hours, the raw materials attached to the wall of the ball mill were scraped off in the glove box. The whole ball milling process required scraping twice.
[0046] (3) Sintering: The powder obtained in step (2) was loaded into a graphite mold with a diameter of 12.7 mm and placed in a spark plasma sintering furnace. During the sintering process, the pressure was increased at a pressure rate of 20 MPa / min, the temperature was increased at a heating rate of 100°C / min, and finally the temperature was kept at 750°C and an axial pressure of 50 MPa for 10 minutes. After the sintering was completed, the pressure was reduced at the same rate, and the sample was cooled to room temperature to obtain a high-density sample.
[0047] The Mg obtained in this example 3.4 Ta 0.3 Sb 1.5 Bi 0.49 Te 0.01 Thermoelectric performance test of materials such as Figure 21-25 The relationship between conductivity and Seebeck coefficient and temperature is shown in Fig.21 and Fig. 22 The conductivity of the sample at room temperature is 752.8S / cm, the Seebeck coefficient is -171.4μV / K, the conductivity at 723K is 239.5S / cm, the Seebeck coefficient is -267.8μV / K, and the Seebeck coefficient is negative in the entire temperature range, indicating that it is N-type. Its power factor is shown in Fig.23 , the power factor at room temperature is 22.1 μW cm -1 mK -2 , the power factor at 723K is 17.2μW cm -1 mK -2 The relationship between thermal conductivity and lattice thermal conductivity and temperature is shown in Fig.24 , the total thermal conductivity at room temperature is 1.17 Wm -1 K -1 , the lattice thermal conductivity is 0.76 Wm -1 K -1 ; The total thermal conductivity at 737K is 0.81 Wm -1 K -1 , the lattice thermal conductivity is 0.54 Wm -1 K-1 Its ZT value changes with temperature as follows Fig.25 As shown, the highest ZT value is 1.57.
[0048] Compared with Example 3, too high Ta concentration leads to decreased material performance. On the one hand, excessive Ta as a +5 valent cation significantly increases the carrier concentration, but also increases the electronic thermal conductivity, thereby weakening the overall thermoelectric performance. On the other hand, Ta doping causes the grain size to increase, the grain boundary effect to weaken, resulting in an increase in thermal conductivity, further limiting performance optimization. Therefore, selecting an appropriate amount of Ta doping concentration is crucial to improving material performance.
[0049] The present invention adjusts the Mg content, compensates for the loss of Mg during the preparation process, reduces Mg vacancy defects, and converts Mg3Sb2 from P-type conductivity to stable N-type conductivity. The ZT value of the P-type Mg3Sb2-based thermoelectric material is only 0.076, while the ZT value of the N-type material can reach 1.32, an increase of 1636%. In addition, by doping the N-type Mg3Sb2-based thermoelectric material with Ta elements, its performance is further significantly improved. The introduction of the Ta element not only fills the inherent Mg vacancies, reduces the internal defects of the material, and improves the carrier mobility, thereby enhancing the electrical properties and maintaining a high power factor; it also generates Ta metal phases and secondary phases in the matrix, forming phonon scattering centers, enhancing phonon scattering, and significantly reducing lattice thermal conductivity. Through the coordinated optimization of electrical and thermal properties, the material prepared by the present invention achieves a maximum ZT value of 1.85, an increase of 38.5%.
[0050] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. An N-type Mg3Sb2-based thermoelectric material, characterized in that: The chemical composition of the Mg3Sb2-based thermoelectric material is: Mg 3+ x Ta y Sb 1.5 Bi 0.49 Te 0.01 , where 0.2<x≤0.6, 0<y<0.
3.
2. The N-type Mg3Sb2-based thermoelectric material according to claim 1, characterized in that: 0.2<x≤0.4, 0<y≤0.
25.
3. The method for preparing the N-type Mg3Sb2-based thermoelectric material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Ingredients: According to the chemical formula Mg 3+x Ta y Sb 1.5 Bi 0.49 Te 0.01 , weigh Mg powder, Sb powder, Bi powder, Te powder and Ta powder as reaction raw materials; (2) ball milling of raw materials: the reaction raw materials weighed according to step (1) are placed in a stainless steel ball mill, the ball mill is filled with inert gas and sealed, and the sealed ball mill is placed on a three-dimensional pendulum ball mill for ball milling to obtain powder; (3) Sintering: The powder obtained by ball milling according to step (2) is loaded into a graphite mold and placed in a spark plasma sintering furnace for spark plasma sintering to obtain a circular sheet material with good density, which is the N-type Mg3Sb2-based thermoelectric material.
4. The preparation method according to claim 3, characterized in that: All steps (1) to (3) are carried out in a glove box filled with argon gas, wherein the oxygen concentration in the glove box is less than 0.1 ppm and the water concentration is less than 0.1 ppm.
5. The preparation method according to claim 3, characterized in that: In step (2), in addition to the reaction raw materials, two stainless steel balls with a diameter of 12 mm and two stainless steel balls with a diameter of 8 mm are placed in the ball mill to crush and mix the raw materials.
6. The preparation method according to claim 3, characterized in that: In step (2), the ball milling time is 12 hours. The raw materials adhering to the ball mill jar are scraped off in the glove box every 4 hours. The whole ball milling process needs to be repeated twice.
7. The preparation method according to claim 3, characterized in that: The ball milling in step (2) uses a MSK-SFM-3-II three-dimensional swing ball mill, wherein the ball mill rotation speed is 1000 r / min.
8. The preparation method according to claim 3, characterized in that: The ball milling procedure in step (2) is: first rotate forward for 15 minutes, stop for 1 minute, then rotate reversely for 15 minutes and stop for 1 minute. The above is one cycle, and a total of 8 cycles are performed.
9. The preparation method according to claim 3, characterized in that: In step (3), the spark plasma sintering temperature is 750° C., the pressure is 50 MPa, and the sintering time is 10 min.
10. The method according to claim 9, characterized in that In step (3), the pressurization rate is 15-20 MPa / min and the heating rate is 100°C / min.